2022
DOI: 10.1038/s41598-022-14049-5
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal phase improves aneuploidy detection in non-invasive prenatal testing at low fetal DNA fractions

Abstract: Non-invasive prenatal testing (NIPT) to detect fetal aneuploidy by sequencing the cell-free DNA (cfDNA) in maternal plasma is being broadly adopted. To detect fetal aneuploidies from maternal plasma, where fetal DNA is mixed with far-larger amounts of maternal DNA, NIPT requires a minimum fraction of the circulating cfDNA to be of placental origin, a level which is usually attained beginning at 10 weeks gestational age. We present an approach that leverages the arrangement of alleles along homologous chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…38 Other laboratories perform deeper sequencing or other additional analyses in response to a low FF and are able to provide results in most cases. 39,40 Low FF and aneuploidy A low FF and nonreportable cfDNA screening have been associated with aneuploidy, particularly trisomies 13, 18, and triploidy. 3,36,41 One meta-analysis reported that when a cfDNA result was not reported, the chance for a common aneuploidy was 5.9%, and the risk was 11.7% for sex chromosome aneuploidy.…”
Section: Nonreportable Cfdna Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Other laboratories perform deeper sequencing or other additional analyses in response to a low FF and are able to provide results in most cases. 39,40 Low FF and aneuploidy A low FF and nonreportable cfDNA screening have been associated with aneuploidy, particularly trisomies 13, 18, and triploidy. 3,36,41 One meta-analysis reported that when a cfDNA result was not reported, the chance for a common aneuploidy was 5.9%, and the risk was 11.7% for sex chromosome aneuploidy.…”
Section: Nonreportable Cfdna Resultsmentioning
confidence: 99%
“…The platform utilized may therefore impact test failure rates, which have been reported to be more common in SNP-based approaches (3% to 6%) when compared with other platforms (1.6%) 38 . Other laboratories perform deeper sequencing or other additional analyses in response to a low FF and are able to provide results in most cases 39,40 …”
Section: Nonreportable Cfdna Resultsmentioning
confidence: 99%